MAKNA DI BALIK HEADLINE BERITA Studi Hermeneutika pada Headline Berita tentang Presiden Yudhoyono di Surat Kabar Online Media Indonesia edisi Juli 2011 - , HENDRO MUHAIMIN, Dr. Phil. Ana Nadhya Abrar, M.E.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Media Indonesia is an online newspaper that headline puts her on topicality and political events that ironic and controversial. Headline news is selected is then displayed with the impression that is free to interpret. Linkage to President SBY, Media Indonesia online provide the truth that is not because the interpreter did not try to understand the text on a news headline to President SBY, but because of its headline that does not convey the totality of the reasons for the message it conveys. So this study will reveal how to interpret the message behind the news headlines about President SBY on the Media Indonesia online newspaper. This research uses a qualitative method that is based on headline at Media Indonesia online newspaper which includes news about the president SBY. The intended use of this hermeneutic analysis is to try to dismantle the ideology or communication messages behind news headlines about President SBY in Media Indonesia. This research may also be called interpretive research, because the outcome data collected represents their interpretation of the data from the object of research. The results of the analysis with the proposition aspect of Gadamer's hermeneutics historiskalitas, dialectical dialogical aspects, aspects lingusitikalitas, and also aspects of the meaning of truth, it is known that the conditions contained in the media headlines Indonesia online in July 2011, described the President as a figure of the president with a high percentage for a headline is negative. Headline is the average found in reporting on economic performance, political, until the performance of his cabinet, which is one field that dominates the news is negative preaching. There is a third party, namely Indonesia online media ideology that governs the process of dialogical dialectic on the interpreter and the headline text which was then deliberately set well meaning and language. That is, the communication message conveyed through the headline on the online newspaper Media Indonesia is a form of message that is not intact.